Contribution to colonic polyposis of recently proposed predisposing genes and assessment of the prevalence of NTHL1‐ and MSH3‐associated polyposes. Issue 11 (29th July 2019) - Terradas, Mariona; Munoz‐Torres, Pau M.; Belhadj, Sami; Aiza, Gemma; Navarro, Matilde; Brunet, Joan; Capellá, Gabriel; Valle, Laura
Abstract: Technological advances have allowed the identification of new adenomatous and serrated polyposis genes, and of several candidate genes that require additional supporting evidence of causality. Through an exhaustive literature review and mutational screening of 177 unrelated polyposis patients, we assessed the involvement of MCM9, FOCAD, POLQ, and RNF43 in the predisposition to (nonserrated) colonic polyposis, as well as the prevalence of NTHL1 and MSH3 mutations among genetically unexplained polyposis patients. Our results, together with previously reported data and mutation frequency in controls, indicate that: MCM9 and POLQ mutations are not associated with polyposis; germline RNF43 mutations, with a prevalence of 1.5–2.5% among serrated polyposis patients, do not cause nonserrated polyposis; MSH3 biallelic mutations are highly infrequent among European polyposis patients, and the prevalence of NTHL1 biallelic mutations among unexplained polyposes is ~2%. Although nonsignificant, FOCAD predicted deleterious variants are overrepresented in polyposis patients compared to controls, warranting larger studies to provide definite evidence in favor or against their causal association with polyposis predisposition.